Autoimmunity co-signaling system: Regulatory T cells, CTLA-4 and FOXP3 (2005)
Co-signaling molecules can act as co-stimulators or co-inhibitors, depending on whether they promote or suppress T-cell activation, respectively. At the specific time and location, co-signaling molecules positively and negatively control antigen presentation, growth, differentiation and function of T-cells. An important cellular group implicated in the regulation of co-stimulation is known as regulatory T cells (Treg). These cells can be used clinically in treatments ranging from cellular transfer in transplant patients to autoimmune diseases and suppression in cancer patients. Treg act through CTLA-4 molecules, which have the ability to suppress the co-stimulation signals and to stop the T cell response. Recently, CTLA-4Ig fusion molecules have been developed, which can block the presentation of auto-antigens. FOXP3 transcription factor is a specific molecule present in Treg that inhibits the production of IL-2 by CD4+ activated cells. Currently, FOXP3 functions are being extensively studied in order to develop new therapeutic targets. This article reviews co-signaling and its mechanism in Treg (CTLA-4, FOXP3), as well as its role in the physiopathology of autoimmune diseases.